Exercise-Based Cardiac Rehabilitation in Patients With Coronary Heart Disease - V. Krasavina, T.; D. Runenko, S.; A. Osadchuk, M.; A. Sultanova, O.; Y. Shelehova, T. (International Journal of Engineering and Technology, 2018)
Objective: to develop a method of physical training programs and select a physical cardiac rehabilitation program in case of severe coronary heart disease (CHD). Materials and Methods: 370 men with CHD with an average age of 54,0 ± 1,6 years were examined. 230 patients were divided into 8 groups, depending on the severity of the disease and the training mode. The complex physical rehabilitation programs included controlled exercise on a cycle ergometer with low intensity using the developed method. The control group of 140 patients did not undergo the recommended programs of physical rehabilitation. All patients underwent cycle ergometry, electrocardiography, echocardiography, blood pressure monitoring. The parameters of hemodynamics, tolerance to physical activity, lethality in the first three years were studied. Results: Inclusion of controlled exercise in the program of cardiac rehabilitation with the low-intensity cycle ergometer increased the maximum oxygen consumption by the myocardium, improved the cardiac contractile function and prognosis reducing the lethality during the first three years of observation. Combination of exercise of low and high intensity under rehabilitation programs of patients with CHD is not appropriate due to the high risk of hypertensive reactions.Conclusions: exercise using a cycle ergometer and the developed method can be used in patients with severe CHD at the hospital and subsequent stages following hospital-based rehabilitation increasing the time but not the power of the exercise.Early exercise activization by patients using the developed method reduces the time spent at the hospital. It is used to prevent hypokinesia complications.
Keywords: cardiac rehabilitation; coronary heart disease; physical training; cycle ergometer training.